Short-term treatment with multi-drug regimens combining BRAF/MEK-targeted therapy and immunotherapy results in durable responses in Braf-mutated melanoma. (1st January 2021) - White, Michael G.; Szczepaniak Sloane, Robert; Witt, Russell G.; Reuben, Alexandre; Gaudreau, Pierre Olivier; Andrews, Miles C.; Feng, Ningping; Johnson, Sarah; Class, Caleb A.; Bristow, Christopher; Wani, Khalida; Hudgens, Courtney; et al.
ABSTRACT: Targeted and immunotherapy regimens have revolutionized the treatment of advanced melanoma patients. Despite this, only a subset of patients respond durably. Recently, combination strategies of BRAF/MEK inhibitors with immune checkpoint inhibitor monotherapy (α-CTLA-4 or α-PD-1) have increased the rate of durable responses. Based on evidence from our group and others, these therapies appear synergistic, but at the cost of significant toxicity. We know from other treatment paradigms (e.g. hematologic malignancies) that combination strategies with multi-drug regimens (>4 drugs) are associated with more durable disease control. To better understand the mechanism of these improved outcomes, and to identify and prioritize new strategies for testing, we studied several multi-drug regimens combining BRAF/MEK targeted therapy and immunotherapy combinations in a Braf -mutant murine melanoma model ( Braf V600E /Pten −/− ). Short-term treatment with α-PD-1 and α-CTLA-4 monotherapies were relatively ineffective, while treatment with α-OX40 demonstrated some efficacy [17% of mice with no evidence of disease, (NED), at 60-days]. Outcomes were improved in the combined α-OX40/α-PD-1 group (42% NED). Short-term treatment with quadruplet therapy of immunotherapy doublets in combination with targeted therapy [dabrafenib and trametinib (DT)] was associated with excellent tumor control, with 100% of mice having NED after combined DT/α-CTLA-4/α-PD-1 or DT/α-OX40/α-PD-1. Notably, tumors from mice in these groups demonstrated a high proportion of effector memory T cells, and immunologic memory was maintained with tumor re-challenge. Together, these data provide important evidence regarding the potential utility of multi-drug therapy in treating advanced melanoma and suggest these models can be used to guide and prioritize combinatorial treatment strategies.